The Relationship Between Social Mobility Belief and Learning Engagement in Adolescents: The Role of Achievement Goal Orientation and Psychological Capital - Xie, Jin; Zhang, Bo; Yao, Zhendong; Peng, Biao; Chen, Hong; Gao, Juan (Frontiers in Psychology, 2022)
Objective:To explore the relationship between adolescents’ social mobility belief and their learning engagement, as well as the mediating effect of achievement goal orientation and the moderating effect of psychological capital. Method:A sample of 895 adolescents from Hunan, Jiangxi, Hainan, Henan, and Guangdong provinces were assessed using the social mobility belief questionnaire, the achievement goal orientation questionnaire, the adolescents’ psychological capital questionnaire, and the adolescents’ learning engagement questionnaire. Results:First,adolescents’ social mobility belief was positively related to their learning engagement(r=0.481, p<.01); Second,the two achievement goal orientations-mastery goal orientations and achievement goal orientations-had mediating effects between social mobility belief and learning engagement;Third,the relationship between achievement goal orientation and learning engagement was regulated by psychological capital. Adolescents with high psychological capital had higher learning engagement. Conclusion:Adolescents’ social mobility belief can directly affect their learning engagement, and it can also indirectly affect their learning engagement through achievement goal orientation moderated by their level of psychological capital. Our findings highlight the importance of providing adolescents with guidance in setting up positive social values and definitions of success while stimulating their psychological capital as a part of the teaching process.